2022
DOI: 10.1002/app.53230
|View full text |Cite
|
Sign up to set email alerts
|

Service performance of GF/Nano‐Al2O3/PA66 sucker rod centralizer in aqueous environment

Abstract: Sixteen groups of GF/Nano‐Al2O3/PA66 composite samples were prepared by injection molding process and orthogonal experimental design method. The water absorption, hardness, compressive strength, and tribological properties under water conditions were measured. The wear surface morphology and material transfer from mate pair were analyzed by scanning electron microscopy (SEM) and energy spectroscopy (EDS). The results show that the minimum friction coefficient of G25A1 ratio is 0.064, which is 54.3% and 72.2% l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It can be observed that the mechanical behavior of the 3D scaffolds underwent significant changes; the PA scaffold was damaged after compression, while the PH10 and PH30 scaffolds maintained their shape without destruction after compression. This is due to the absorption of water by PA66 in the aqueous environment, leading to the relaxation of polymer chains, which in turn altered the mechanical behavior of the scaffolds . The addition of HA apatite may counteract this effect, to some extent.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the mechanical behavior of the 3D scaffolds underwent significant changes; the PA scaffold was damaged after compression, while the PH10 and PH30 scaffolds maintained their shape without destruction after compression. This is due to the absorption of water by PA66 in the aqueous environment, leading to the relaxation of polymer chains, which in turn altered the mechanical behavior of the scaffolds . The addition of HA apatite may counteract this effect, to some extent.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This is due to the absorption of water by PA66 in the aqueous environment, leading to the relaxation of polymer chains, which in turn altered the mechanical behavior of the scaffolds. 52 The addition of HA apatite may counteract this effect, to some extent. Our test results indicate that although there was a decline in mechanical properties after soaking in PBS, the compressive strength and elastic modulus of the PH30 composite scaffolds remained within acceptable ranges, similar to glenoid cancellous bone strength (6.7−17 MPa) (Figure S15, Table S1).…”
Section: Mechanics and Fracturementioning
confidence: 99%